Sindrom Infus Terkait Propofol: Diagnosis dan Penatalaksanaan: Tinjauan Pustaka - Hariyanto, Hori; Oktaviani Pandrya, Carla; Anderson Surya, Kevin (Cermin Dunia Kedokteran, 2026)
Propofol-related infusion syndrome (PRIS), first described in 1990, is a rare and dangerous condition caused by high-dose (> 4 mg/kg/hour) and prolonged (> 48 hours) administration of propofol in mechanically ventilated patients. This condition is characterized by a progressive constellation of multi-organ failure. The main clinical presentations include severe metabolic and lactic acidosis, rhabdomyolysis, acute liver failure, lipemic blood, hyperkalemia, and cardiovascular impairment or marked bradycardia, which can lead to cardiac arrest. The mechanism of PRIS remains unclear and is likely controversial. The most effective way to prevent PRIS is to remain vigilant and maintain a high level of suspicion during prolonged propofol administration. Early recognition of clinical manifestations, prompt discontinuation of propofol infusion, and timely initiation of supportive management are essential to reduce morbidity and mortality associated with PRIS. Understanding the underlying pathophysiology and identifying patients at high risk may improve preventive strategies and optimize outcomes in critically ill patients receiving prolonged propofol infusion.